Enhancement of Undergraduate Students’ Competency in Creating English Learning Innovation through Hybrid Learning with Peer Coaching - Teeraporn Plailek; Abigail M. Essien; Yothin Sawangdee (Journal of Educational Issues, 2024)
A high level of competency is required for everyone’s progress. The ability to innovate has an impact on one’s ability to learn. This research aims to 1) compare students’ innovation knowledge achievement in creating English learning innovation before and after using hybrid learning with peer coaching; 2) study students’ skills in creating English learning innovation after using hybrid learning with peer coaching; and 3) study students’ attitude towards hybrid learning with peer coaching. Samples used in this research were selected by a simple random sampling method which included 63 second-year English major undergraduate students from one university in Thailand. The instruments used in this study include knowledge tests on innovation, innovative skills assessment form, and attitude questionnaires for innovation. The data obtained were analyzed by the applications of mean, standard deviation, and t-test. The results showed that 1) students’ learning achievement in creating English learning innovation after using hybrid learning with peer coaching was higher than before with statistically significant at the level of .05; 2) students’ skills in creating English learning innovation was at a high level; 3) students had the highest level of attitude towards hybrid learning with peer coaching.